Effect of different surfactants on removal efficiency of heavy metals in sewage sludge treated by a novel method combining bio-acidification with Fenton oxidation - Ren, Miao-miao; Yuan, Xing-zhong; Zhu, Yi; Huang, Hua-jun; Zeng, Guang-ming; Li, Hui; Chen, Ming; Wang, Hou; Chen, Chang-ya; Lin, Ning-bo (Journal of Central South University, 2014)
The aim of this work was to investigate the effect of different surfactants on the removal efficiency of heavy metals in sewage sludge treated by a method combining bio-acidification with Fenton oxidation. Four surfactants were adopted such as anionic surfactant (sodium dodecyl benzene sulfonate, SDBS), nonionic surfactants (tween-20 and tween-60) and cationic surfactant (hexadecyl trimethyl ammonium chloride, HTAC), respectively. The indigenous sulfur-oxidizing bacteria in bio-acidification phase were enriched and cultured from fresh activated sludge obtained from a wastewater treatment plant. It is shown that different surfactants exhibited distinct effect on the removal efficiency of heavy metals from sewage sludge. The nonionic surfactants, especially tween-60, promotes the solubilization of heavy metals, while the anionic and cationic surfactants hinder the removal of heavy metals. Copper is efficiently leached. The removal efficiency of cadium is relatively lower than that of Cu due to the demand for rigorous pH value. Lead is leached with a low efficiency as the formation of low soluble PbSO 4 precipitates.